Creative Ethical Practice in Counselling and Psychotherapy ; GSC002095 - Owens, Patti; Springwood, Bee; Wilson, Michael (London, Thousand Oaks, Calif : SAGE, 2012)
Owens et al., who are humanistic and integrative therapists in the UK, explain how counselors and psychotherapists can ensure their work with clients is ethical and creative. They argue that ethical practice combines safety and creativity, and that it is the responsibility of practitioners to be personally and professionally aware of ethical issues and be willing to work through them with the client. They explore the tension between ethics and the values of consumer culture and the rise in complaints against therapists; the cornerstones of good practice, such as boundaries, the philosophical and theoretical frame, the primacy of the therapeutic relationship, intervention methods and styles, and therapist self-care; the importance of therapeutic agreements; framing the therapeutic process; dealing with mistakes; and reviewing personal and professional experience to develop ethical and creative practice. They draw on situations from their own experiences as clients, therapists, supervisors, and trainers to illustrate the personal and professional attitudes and behaviors of the therapist, and their self-awareness and understanding of the client's experience. Students and trainee therapists can also benefit from the book. Annotation ©2012 Book News, Inc., Portland, OR (booknews.com)
Includes bibliographical references and index
Keywords: Counseling -- Moral and ethical aspects; Psychotherapy - Moral Ethics; Ethical Therapy; Professional Ethics; Psychotherapist - Ethics; Counsellors Ethics